Why coaches should encourage swimmers` efforts to succeed - Solstad, B. E.; Lemyre, P. N. (Journal of Swimming Research, 2014)
Achievement Goal Theory (AGT; 11 , 21 ) assumes that properties of the achievement situation in which swimmers find themselves are central to the motivation process. The premise of this line of research is that athletes' experiences in sports and their interpre tation of those experiences influence the degree to which a mastery-involving motivational climate or an ego-involving motivational climate are perceived as salient. Thus, the focus of the current study was to assess how mastery-involving or ego-involving motivational climates arise from different types of coaching behaviors . Additionally, we examined how perceived motivational climates, associated to different coaching behaviors, influenced important parameters, such as intrinsic motivation, subjective well-being, and athlete burnout. Participants were 202 swimmers (range 1424, M = 16.4, SD = 2.3), who represented competitive levels from novice competitors to world championship athletes, but where the majority of the athletes had competed up to the national level. Results revealed that swimmers perceived a mastery-involving climate when their coaches emphasized positive reinforcement, mistake-contingent encouragement, corrective instruction given in a positive and encouraging fashion, and proper technical i nstruction. On the other hand, coaching behavior emphasizing punitive technical instruction was associated with the perception of an ego-involving climate on the swim team. Further, analyses revealed a positive association between the perception of an ego-involving climate and symptoms of athlete burnout, while the perception of a mastery-involving climate was associated with higher levels of intrinsic motivation and subjective well-being.